A DC Fault Location Method of Multiterminal Flexible DC Distribution Network. (24th February 2022) - Wang, Chenqing; Li, Peng; Xu, Xiao; Gao, Hui
Abstract : Multiterminal flexible DC distribution network is a complex system made up of many power-electronic devices. Its diversified and comprehensive fault characteristics are featured by multiperiod and strong transient. This paper starts with investigating the mechanisms of typical DC short circuit faults of the MMC-based system. Then, a typical flexible DC distribution network is built in PSCAD to analyse the characteristics of its pole-to-pole short-circuit fault and pole-to-ground fault. With the aid of the above findings, a fault detection and location method is proposed with its effectiveness evaluated through simulations.